2014
DOI: 10.4143/crt.2014.46.3.234
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Oral Paclitaxel with a Novel P-Glycoprotein Inhibitor, HM30181A, in Patients with Advanced Solid Cancer

Abstract: PurposeThe purpose of this study is to determine the maximum tolerated dose (MTD), safety, pharmacokinetics, and recommended phase II dose of an oral drug composed of paclitaxel and HM30181A, which is an inhibitor of P-glycoprotein, in patients with advanced cancers.Materials and MethodsPatients with advanced solid tumors received standard therapy were given the study drug at escalating doses, using a 3+3 design. The study drug was orally administered on days 1, 8, and 15, with a 28-day cycle of administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The reason for the paclitaxel persistence in tumors remains unclear; however, based on the mechanism of DHP107, we can make a few assumptions regarding DHP23002. DHP23002 can prolong the release of paclitaxel in the intestine to enhance the absorption and stability of the drug in the tumor and can evade the action of P-glycoproteins [17–18]. In a PK experiment conducted on large animals, DHP23002 showed similar PK patterns, and it was confirmed that an effective paclitaxel concentration was maintained in blood for a prolonged period even when low doses were administered (S2 Fig).…”
Section: Discussionmentioning
confidence: 86%
“…The reason for the paclitaxel persistence in tumors remains unclear; however, based on the mechanism of DHP107, we can make a few assumptions regarding DHP23002. DHP23002 can prolong the release of paclitaxel in the intestine to enhance the absorption and stability of the drug in the tumor and can evade the action of P-glycoproteins [17–18]. In a PK experiment conducted on large animals, DHP23002 showed similar PK patterns, and it was confirmed that an effective paclitaxel concentration was maintained in blood for a prolonged period even when low doses were administered (S2 Fig).…”
Section: Discussionmentioning
confidence: 86%
“…In addition, mice with intra-cerebrally implanted tumor cells show increased apoptosis of tumor cells in brain tumors after co-oral administration of HM and PTX. A recent phase I clinical study investigating the use of an oral drug containing PTX and HM for the treatment of advanced solid tumors, such as cancers of the breast, pancreas, and gallbladder, has suggested the relative safety of HM PTX co-treatment in clinical practice 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This can be done by using inhibitor to block the P-gp efflux. Indeed, coadministration of the therapeutic agents and P-gp inhibitors in their free forms may reduce the expulsion of the agents by P-gp and increase the intracellular drug concentration 15 , 16 . Nevertheless, P-gp pumps also play a crucial physiological role in protecting tissues from poisonous xenobiotics and endogenous metabolites that are widely distributed throughout the body 17 19 .…”
Section: Introductionmentioning
confidence: 99%